FAKTOR-FAKTOR UTAMA CAGAR BUDAYA RUMAH LONTIOK DI DESA PULAU BELIMBING SEBAGAI KEBUDAYAAN MELAYU RIAU - AMELIA AGUSTINA; HAIDA SAQILIA; JUNITA FRANSISCA; MELY NOVRIANI; NURUL IKHWANI; PUTRIANA KARTIKA WULANDARI; SASABILA RAMADHANI; HAMBALI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Lontiok House is a house located in one of the villages, precisely on Belimbing Island, Kampar Regency, Riau Province. This traditional house is one of the typical houses of the Malay community that has high historical and cultural value. This study aims to determine the meaning of culture, social function, and the reasons why Lontiok House is considered a Malay cultural heritage in the Riau area. This study uses a qualitative descriptive method by means of observation, interviews with house guards, and documentation collection. The results of the study show that Lontiok House is a stilt house with a curved roof (lontiok) which symbolizes respect for God Almighty. This house also applies the philosophy of odd numbers in its building, which is believed by the community to be a symbol of balance and good luck. In the past, Lontiok House was used as a place for traditional deliberations and community activities, while now it is often used for social and religious events such as the People's Party, MTQ, and student KKN. Although many traditional heritage items were lost due to theft, Lontiok House is still recognized as a historical building that has important cultural and architectural value. Therefore, the Lontiok House needs to be maintained and preserved as a Kampar Malay cultural heritage.